PHENOTYPIC EVALUATION OF EIGHT ONION (Allium cepa L.) CULTIVARS GROWN IN NORTHERN NIGERIA - Yuguda,U.A.; Ismaila, M.; Zhigila, D.A.; Karu, E. , (BIMA JOURNAL OF SCIENCE AND TECHNOLOGY (2536-6041), 2017)
Allium cepa is the most important Allium species and the second most important vegetable crop in the world. Onion production is low in North-eastern Nigeria compared to the North-west despite the suitable soil and environmental condition. This could be attributed to the inappropriate identification information which leads to cultivation of unsuitable varieties. The phenotypic variability in onions were quantified in order to allow an effective use of cultivar collections. Eight (8) onions (A. cepa) cultivars were collected from different onion growing regions in northern Nigeria. Randomized complete block design with replications was used. Foliage and bulb traits were analysed. Significant differences were observed between cultivars and Wuyan bijimi recorded longest leaf (60.54±5.48cm) and leaf index. Phenotypic differences were recorded, however, homogeneity was recorded for few traits.